Sistem Manajemen Pengelolaan Keuangan Berbasis Android pada Appel Specialist Repair - Saputra, Anggi; Zulkarnain, Iskandar; Fauziyah, Fauziyah (Jurnal SITECH : Sistem Informasi dan Teknologi, 2023)
Appel Specialist Repair is a business that operates in Smartphone and Computer repair and maintenance services. Currently, the financial management process uses Google services, namely spreadsheets, and recording is still done manually, such as recording financial transactions, checking stock of goods, and preparing financial reports. This manual approach carries the risk of data duplication and accidental data deletion. The research method used in this research is a qualitative method consisting of literature studies related to the thesis title, field studies observations at Appel Specialist Repair, interviews with related parties, analysis of needs related to the system required, design and creation of an Android-based information system, and testing black box financial management application. Based on the research and analysis, UML models for designing and creating an Android-based financial management information system for Apple Specialist Repair in its finance.